Comparing the contribution of conscientiousness, self-control, and grit to key criteria of sport expertise development. (January 2018) - Tedesqui, Rafael A.B.; Young, Bradley W.
Abstract: In order to develop expertise, athletes need to amass a high volume of deliberate practice activities over a long period of time. Three personality traits that conceptually relate to long-term goal pursuits and that have been linked to achievement outside sport are conscientiousness, self-control, and grit. This investigation examined how conscientiousness, alone (Study 1) and compared to self-control and grit (Study 2), explained criteria related to sport expertise development. Athletes ( N = 270, 125 female, M age = 21.27, SD = 6.91) ranging in skill level (local to international) completed surveys for personality, deliberate practice (DP), engagement in practice contexts (mandatory and optional), and threats to commitment (thoughts about quitting or switching out of one's sport). In Study 1, broad conscientiousness predicted engagement in both contexts of practice and fewer threats to commitment. At the facet-level, achievement-striving was the best predictor of DP and engagement in practice contexts. No conscientiousness facets predicted threats to commitment or higher skill group membership. In the comparative analyses between facets of conscientiousness, self-control, and grit (Study 2), grit variables performed best: perseverance of effort explained deliberate practice and higher skill group membership and consistency of interests associated with less thoughts of quitting/switching out of sport. Achievement-striving, dutifulness and self-discipline also showed effects associated with key criteria. These findings suggest, for example, that screening for perseverance of effort may help talent selectors identify which athletes have a personality advantage to persevere through the highly effortful conditions of DP. Other talent identification and development implications are discussed. Highlights: Specific personality facets were associated to criteria for expert sport development. Grit facets were better predictors than conscientiousness and self-control facets. Of 10 initial facets, two grit facets and achievement-striving proved important. Perseverance related to practice; consistency of interests related to commitment. Athletes high in perseverance were much more likely to be in the expert group.